A LOW-LOAD-TRUNCATION METHOD FOR FATIGUE CRACK GROWTH TESTS - ZHANG HaiYing; DONG DengKe; CHEN Li; ZANG WeiFeng; YAN WenWei (Jixie qiangdu)
Based on the dependence of fatigue crack growth（ FCG） threshold on stress ratio,a low-load-truncation method for FCG tests is proposed. The effects of FCG property,stress amplitude and stress ratio are considered by this method. FCG tests using middle tension（ M（ T）） specimens under a flight-by-flight spectrum and two truncated spectra were conducted. The difference between FCG lives under truncated spectra and those under baseline spectrum is less than 26%,but the test duration were shorten by 78% maximum. The test results indicate that the proposed low-load-truncation method can shorten FCG test period effectively without changing the failure mode or changing the FCG life irrationally.